Organ procurement surgery as a means of increasing open surgical experience during urology residency - Hoag, Nathan A; Flannigan, Ryan; MacNeily, Andrew E (Canadian Urological Association Journal, 2014)
Introduction: The introduction and advancement of minimally invasive surgery (MIS) has resulted in a reciprocal decline in exposure to open surgery during urology residency training. We propose organ procurement surgery as a potential vehicle to facilitate an increase in open surgical experience among trainees. We define the surgical case volume for organ procurement surgeries currently performed by urology residents in Canada, and determine what capacity exists for expansion. Methods: Data on organ procurement surgeries were extracted for Canadian urology residents case-logs between 2005 and 2009. Case-logs were anonymously analyzed through the voluntary self-reporting program T-Res (Resilience Software Inc.). National deceased organ donor data were obtained from the Canadian Institute for Health Information. Results: The graduating Canadian urology resident has performed an average of 0.95 organ procurement surgeries during 5 years of training. An average of 469.6 procurement surgeries were performed yearly in Canada between 2005 and 2009. The theoretical capacity exists for each graduating resident to perform an additional 16.3 organ procurements during residency. Conclusions: With the establishment of MIS as standard of care for many urologic surgeries, the decrease in open operative experience is concerning. Innovative ways to enrich open surgical experience may be required, and increased formal incorporation of organ procurements into urology residency training curriculum may help fill the void.